Menurunkan Lead Time Test Bench Engine Dengan Meningkatkan Kualitas Cooling System Pada Test Bench - Wilarso, Wilarso; Saepudin, Asep; Idianto, Bayu; Domodite, Aswin (Creative Research in Engineering (CERIE), 2023)
The engine is currently overheating because the cooling system’s temperature increased by 80 oC after the overhaul. A "bench engine test," often referred to as a "assembly engine performance test," must be performed to measure the temperature rise before the engine is given to the customer. The test findings indicate that the PRC PT X standard engine is suitable for supplying SITE clients with high-quality components. In order to be corrected or prevented through engineering, the proposal identifies the root cause of the cooling system dynoÂ test engine issue. The dyno test engine at PRC PT X is being tested in this investigation using the flow method. After the repairs, the cooling tower’s output has cooled down and is now ready to be injected into the engine system at a temperature between 35 and 40 Â°C. This takes place as a result of the heat exchanger’s ability to operate at peak efficiency. When executing a Komatsu engine performance test, all systems, starting with the fuel, oil, water, and electrical sensors, must be in working order and comply withÂ manufacturer-required standard indicators. This will eventually lead to the testing process evolving into a quality method. Therefore, a quality process will result in a quality output.